2018
DOI: 10.1051/0004-6361/201833841
|View full text |Cite
|
Sign up to set email alerts
|

Dust attenuation and Hα emission in a sample of galaxies observed with Herschel at 0.6 < z < 1.6

Abstract: Context. Dust attenuation shapes the spectral energy distribution of galaxies. It is particularly true for dusty galaxies in which stars experience a heavy attenuation. The combination of UV to IR photometry with the spectroscopic measurement of the Hα recombination line helps to quantify dust attenuation of the whole stellar population and its wavelength dependence. Aims. We want to derive the shape of the global attenuation curve and the amount of obscuration affecting young stars or nebular emissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 72 publications
7
82
0
Order By: Relevance
“…This is expected since Charlot & Fall (2000) built their model to reproduce the properties of the starburst galaxies analyzed by Calzetti et al (1994). However a significant difference is visible for λ > 0.5 µm: CF00 is much flatter than C00 (Chevallard et al 2013;Lo Faro et al 2017;Buat et al 2018). The average LF17 law is flatter than the two previous laws over the full wavelength range.…”
Section: Attenuation Lawsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is expected since Charlot & Fall (2000) built their model to reproduce the properties of the starburst galaxies analyzed by Calzetti et al (1994). However a significant difference is visible for λ > 0.5 µm: CF00 is much flatter than C00 (Chevallard et al 2013;Lo Faro et al 2017;Buat et al 2018). The average LF17 law is flatter than the two previous laws over the full wavelength range.…”
Section: Attenuation Lawsmentioning
confidence: 88%
“…It has recently been shown that effective attenuation laws are far from universal but actually vary in local and more distant galaxies (e.g., Salmon et al 2016;Salim et al 2018;Buat et al 2018). The attenuation law appears to flatten out when the amount of obscuration increases, a trend that is predicted by radiation transfer models in dusty media with idealized geometries (Chevallard et al 2013, and references therein) or more realistic distributions from hydrodynamical simulations (Jonsson et al 2010;Roebuck et al 2019;Trayford et al 2019).…”
Section: Introductionmentioning
confidence: 98%
“…An important caveat in SED fitting codes is the use of idealised attenuation curves, converted from extinction laws that do not fully incorporate the effect of the relative geometries expected to be found between dust and stars. In a recent effort to address this caveat, Buat et al (2018) measured the shape of the attenuation curves of star-forming galaxies by employing two different recipes: a flexible Calzetti attenuation law (Noll et al 2009) and a two power-law recipe based on the one inferred by Charlot & Fall (2000). Both recipes take the shape of the attenuation curve and the relative attenuation of young and old stellar populations as free parameters.…”
Section: Attenuation Lawmentioning
confidence: 99%
“…Commonly used codes such as MAGPHYS and CIGALE (da Cunha et al 2008;Noll et al 2009) treat attenuation toward the birth-clouds and in the diffuse ISM separately, which allows for more flexible effective attenuation curves. However, recent work suggests there may need to be additional modification to allow for greater flexibility (Charlot & Fall 2000;Lo Faro et al 2017;Buat et al 2018). Both observational and theoretical studies have shown that such flexibility is required since a single attenuation curve is not appropriate for all star-forming galaxies either locally or at high-z (e.g.…”
Section: Introductionmentioning
confidence: 99%